Human-wildlife conflict in a ‘successful’ community conservation programme: Economic and territorial impacts on Namibia’s conservancies - Gargallo, E. (Journal of Arid Environments, 2021)
Since the 1990s Namibia's Conservancies have been depicted as one of the most successful examples of Community Conservation. The growth in game numbers caused by the conservation programme, however, has led to an increase in Human-Wildlife Conflict (HWC) incidents. These include damages to crops and to infrastructure, the killing of livestock, attacks on humans, and higher levels of psychological stress among affected populations. Local voices often express the feeling that neither compensation payments nor conservation-related benefits outweigh HWC costs. Furthermore, HWC has territorial impacts: it is leading to more restricted access to some areas of land and it reinforces government and NGO discourses in favour of conservation rather than agropastoral land uses. Through the analysis of some specific case-studies we will try to understand these processes, to provide a nuanced view of events on the ground and to explore the potentialities and difficulties of combining wildlife and agropastoral activities on the same lands. It will be shown how, even in reasonably successful conservation schemes, it is difficult to provide rural residents with benefits that would offset HWC costs, and how, most importantly, contrary to the initial Community Conservation ideas of coexistence of human and wildlife populations in open areas, HWC and the measures advocated to prevent it are pushing for stricter boundaries and growing enclosure of separate areas for humans and fauna.